Social Work Initiatives for the Inclusion of Students with Special Educational Needs. Issue 2 (15th March 2017) - Kwan, Vivien; Cheung, Johnson Chun-Sing
Abstract : Based on first-hand experiences in implementing a volunteer mentorship scheme, the authors suggest that the children and youth service centres provide a crucial platform for social workers to engage students with special educational needs (SENs), and it is of the utmost importance to reclaim advocacy for them in social work services. As for the past decade, inclusive education in Hong Kong has received more complaints than compliments regarding the necessary support that SEN students deserve. By adopting a whole-school approach, developmental guidance for these students has been confined mainly to the duties of teachers and teaching assistants in overcrowded classrooms. Without an adequate supply of professional training and in-house support, the practicality of including SEN students in mainstream schooling has been far from satisfactory. This paper supports a social work approach that facilitates the inclusion of SEN students in the community through embracing the divergence of individual characteristics.